The Effect of Blended Learning Model Assisted Video Animation to the Motivation and Learning Outcomes of Science - Assyifa Mega Utami; Nurrohmatul Amaliyah (Postgraduate, University of Mataram, 2022)
The aim of the study is to know there is or not the influence of using blended learning assisted video animation on the motivation and studentsâ€™ learning outcomes of science students of class fifth grade at Cilangkap 01 Pagi elementary school. This study is quantitative research using Quasi Experiment with type Posttest-Only Control Group Design. The study population is all fifth-grade students at Cilangkap 01 Pagi Elementary School in the second semester of the academic year 2021/2022. Sampling used Cluster Random Sampling. The samples of this research are 60 students from classes V-C and V-D. The instrument used a multiple-choice test consisting of 20 questions and a motivational questionnaire with 25 questions. Research data has been tested for normality, then obtained data were normally distributed. Hypothesis testing was using a t-test of tcount= 3.4983 which resulted in the rejection of H0Â at a significance level of about 5% with an effect size of 0.8063 is high in learning outcomes. While the average value of motivation in the experimental class is 60.89 and, in the control, class is 56.57 with an effect size of 0.46 is medium. This study concluded that there is the effect of the use blended learning model assisted video animation to the motivation and students